2018
DOI: 10.1177/0023677217744587
|View full text |Cite
|
Sign up to set email alerts
|

Classification and reporting of severity experienced by animals used in scientific procedures: FELASA/ECLAM/ESLAV Working Group report

Abstract: Directive 2010/63/EU introduced requirements for the classification of the severity of procedures to be applied during the project authorisation process to use animals in scientific procedures and also to report actual severity experienced by each animal used in such procedures. These requirements offer opportunities during the design, conduct and reporting of procedures to consider the adverse effects of procedures and how these can be reduced to minimize the welfare consequences for the animals. Better recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 43 publications
(47 reference statements)
0
55
0
4
Order By: Relevance
“…Severe projects / procedures should be accepted only exceptionally, if the benefits are significant and refinement techniques are not available. As in the rest of the EU countries, the severity assessment is a problem, and it has been established that severity degree will be described and given for each procedure (Smith et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Severe projects / procedures should be accepted only exceptionally, if the benefits are significant and refinement techniques are not available. As in the rest of the EU countries, the severity assessment is a problem, and it has been established that severity degree will be described and given for each procedure (Smith et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We have developed a tool that enables evidence-based severity assessment. With the algorithm presented, an arbitrary number of outcome variables can be used to compute a composite score for welfare assessment and severity grading 1719 . To our knowledge, this is the first attempt in preclinical science to combine phenotypical data using matrices of standardized differences to weigh variable contributions as a means for obtaining a measure for relative severity grades.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that bottom areas are clearly vital for the proper growth of this species in captivity and that the present density of 24 cuttlefish breeders per tank is suitable. On the other hand, considering a retrospective severity analysis (Smith D. et al, 2018), the nonnatural mortality observed during the growth stage raises issues related to the welfare of cuttlefish in this kind of studies. Thus, despite Directive 2010/63/EU provide exemption for studies carried out for veterinary and zootechnical purposes, we believe that the cephalopod community should consider prospective severity assessment analysis to be carried out in all instances (Smith D. et al, 2018;Cooke et al, 2019) and the application of the PREPARE guidelines (Smith A.J.…”
Section: Growthmentioning
confidence: 99%